Giriama and Digo dance styles - Briginshaw, Valerie A. (International Library of African Music, 1987)
It is often said in Kenya that people living on the Kenyan coast 'really know how to dance' and 'their dances are really important to them'. These statements refer to the dancing of the Giriama and Digo peoples. They inhabit the Kenyan coastal strip from Malindi in the North, to the Tanzanian border in the South; the Giriama living to the North of Mombasa and the Digo to the South.
Keywords: African Music